(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2013)
This research aims at studying the relation between fair value and the Financial Reports Quality to achieve a number of aims such as :- 1- Throw light on the problems of the measurement that depends on the historic cost as it paves the way towards the method of the fair value in the accounting measurement. 2-Give a general definition for fair value in the accounting via analyzing the theoretical aspects that relates the subject and the scientific bases on which the relating accounting treatment depend. 3- Exhibit the characteristics that could be added by the fair value to the accounting Information . The study problem is summarized in that the economic and financial variables and changes that the business witnessed had affected, negatively, the real measurement and the accounting disclosure due to the nonsufficient application of the historic cost method depending on the prices change phenomena, hence the study problem is to find another method of measurement to be the comparative modern method of fair value rather than the historic cost method. The study concluded the following :- 1-The fair value accounting of the financial estates has an essential effect on improving the informational contents of the financial reports. 2- Depending the fair value accounting standards makes the financial data an important instruments for management to evaluate the Financial Performance Indications within an economic futuristic due to the relation of these indications with the present and future rather than the past. Hence the study recommend adopting the fair value accounting as a base for the measurement and disclosure Accounting in the supplementary disclosure to prepare the financial reports with high quality and to fulfill the international accounting standards requirements , so applying the fair value accounting is a basic requirement to establish a stock market that can attract the local and foreign investments.